2007
DOI: 10.1002/jae.937
|View full text |Cite
|
Sign up to set email alerts
|

Discounting the distant future: How much does model selection affect the certainty equivalent rate?

Abstract: Evaluating investments with long-term consequences using discount rates that decline with the time horizon, (Declining Discount Rates or DDRs) means that future welfare changes are of greater consequence in present value terms. Recent work in this area has turned towards operationalising the theory and establishing a schedule of DDRs for use in cost benefit analysis. Using US data we make the following points concerning this transition: i) model selection has important implications for operationalising a theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
166
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(172 citation statements)
references
References 35 publications
2
166
3
1
Order By: Relevance
“…Yet, these results were shown to be highly sensitive to the time-series model used to characterize interest rate uncertainty. Subsequent work by Groom, Koundouri, Panopoulou and Pantelidis [25] (henceforth GKPP) showed that more flexible characterizations of interest rate uncertainty lead to a schedule of DDRs that raises the SCC yet further to $14.4/tC. Similar results have been found in many different countries and also when a global perspective is taken [28,22].…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…Yet, these results were shown to be highly sensitive to the time-series model used to characterize interest rate uncertainty. Subsequent work by Groom, Koundouri, Panopoulou and Pantelidis [25] (henceforth GKPP) showed that more flexible characterizations of interest rate uncertainty lead to a schedule of DDRs that raises the SCC yet further to $14.4/tC. Similar results have been found in many different countries and also when a global perspective is taken [28,22].…”
Section: Introductionsupporting
confidence: 57%
“…Qualitatively speaking, Figures 3 and 4 show that persistence again declines towards the more recent windows of data containing a greater proportion of the post-1949 real interest rate series. More importantly, when the data is smoothed 10 See GKPP for the US and [24] for the UK. 11 The ADF test contains the lagged difference terms appropriate for the AR(4) model.…”
Section: Historical Data On Us Interest Ratesmentioning
confidence: 99%
See 3 more Smart Citations